Pengaruh Sistem Digitalisasi Administrasi Perpajakan, Kompetensi Penggunaan, Kesiapan Penerapan Single Identity Number (SIN) Terhadap Ketepatan Pelaporan Perpajakan - Berliani, Annisa; Hartati, Lesi; Munandar, Aris (SUSTAINABLE, 2025)
This study aims to analyze the influence of the digitalization of tax administration systems, user competence, and readiness for implementing the Single Identity Number (SIN) on the accuracy of tax reporting among employees of the Population and Civil Registry Office of South Sumatra Province. A quantitative approach was applied by collecting data through questionnaires from 51 respondents. The findings reveal that all three independent variables significantly affect tax reporting accuracy. Digital tax administration enhances reporting efficiency, user competence reduces errors, and SIN implementation readiness strengthens data integration and reporting accuracy. This research offers strategic insights for improving tax compliance through administrative system development and employee training